2011
DOI: 10.1002/ajh.22202
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury during leukocyte engraftment after autologous stem cell transplantation in patients with light‐chain amyloidosis

Abstract: Engraftment syndrome (ES) is a complication of hematopoietic stem cell transplantation characterized by fever, rash, and non-cardiogenic pulmonary edema. Acute kidney injury (AKI) has been recognized but is considered a minor criterion in one and excluded another definition of ES. We have noted a high incidence of AKI in patients with immunoglobulin light-chain amyloidosis (AL) undergoing autologous stem cell transplant (ASCT) around the time of leukocyte engraftment. This study was conducted to further invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Acute kidney injury, edema, fever, diarrhea, rash, and transient encephalopathy were observed in 93%, 93%, 83%, 69%, 48%, and 17% of patients, respectively 29 . Carerras et al reported a high incidence (12/25; 48%) of ES in patients with amyloidosis 2 .…”
Section: Engraftment Syndrome In Light Chain Amyloidosismentioning
confidence: 98%
“…Acute kidney injury, edema, fever, diarrhea, rash, and transient encephalopathy were observed in 93%, 93%, 83%, 69%, 48%, and 17% of patients, respectively 29 . Carerras et al reported a high incidence (12/25; 48%) of ES in patients with amyloidosis 2 .…”
Section: Engraftment Syndrome In Light Chain Amyloidosismentioning
confidence: 98%
“… 58 Acute kidney injury can frequently occur in patients with AL amyloidosis who have other features associated with engraftment syndrome in the setting of ASCT. 59 This syndrome is characterized by rash, fever, weight gain, diarrhea, and noncardiogenic pulmonary edema within days of leukocyte engraftment. Other causes of acute kidney injury around the time of engraftment, particularly infection, need to be excluded.…”
Section: Risk Stratification and Response Assessmentmentioning
confidence: 99%
“…in younger patients with myeloma, the standard procedure consists of consolidation with high-dose melphalan chemotherapy, followed by autologous stem cell transplantation. This treatment can be administrated to patients with severe kidney dysfunction caused by MGrS, but significant morbidity and mortality must be taken into account [37,38].…”
Section: Treatment Elimination Of Monoclonal B Clonementioning
confidence: 99%